2015
DOI: 10.1186/s12957-015-0485-x
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal study of gender differences in quality of life among Japanese patients with lower rectal cancer treated with sphincter-saving surgery: a 1-year follow-up

Abstract: BackgroundUp to 80% of patients with rectal cancer undergo sphincter-saving surgery, and almost 90% of them experience subsequent physical changes. The number of studies on gender differences in response to this surgery has increased, and the connection between gender and symptoms and patient outcomes has generated increasing interest. Nevertheless, little is known about the gender differences in quality of life and cancer-related symptoms. We examined gender differences and quality of life changes over a 1-ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…On the other hand, among men, fatigue, weight loss, future prospects and role performance was affected by defecation problems and financial difficulties. (21) It is observed that cancer and the effects produced by its treatment lead to important changes in the life of patients, including difficulties of defecation/incontinence and weight loss -which impacts on the perception of the body image -elements that are corroborated by other studies. In addition, pain and fatigue deriving from treatment may explain the poor quality of life presented by men in relation to sexual activity and arousal.…”
Section: Discussionmentioning
confidence: 70%
“…On the other hand, among men, fatigue, weight loss, future prospects and role performance was affected by defecation problems and financial difficulties. (21) It is observed that cancer and the effects produced by its treatment lead to important changes in the life of patients, including difficulties of defecation/incontinence and weight loss -which impacts on the perception of the body image -elements that are corroborated by other studies. In addition, pain and fatigue deriving from treatment may explain the poor quality of life presented by men in relation to sexual activity and arousal.…”
Section: Discussionmentioning
confidence: 70%
“…Furthermore, it is hypothesised in many QOL studies among patients receiving SSS that bowel function or faecal incontinence score influences HRQOL. Kinoshita et al (2015) showed that global health status score of EORTC QLQ-C30 was affected by defecation problems at 1 month after SSS.…”
Section: Discussionmentioning
confidence: 98%
“…Kinoshita et al . () showed that global health status score of EORTC QLQ‐C30 was affected by defecation problems at 1 month after SSS.…”
Section: Discussionmentioning
confidence: 99%
“…While much is known on the quality of life of cancer survivors in general, not much is known about the effects of an individual's gender on overall quality of life. Additionally, there are conflicting results as to whether there are gender differences in quality of life (Arden-Close et al, 2011;Giesinger et al, 2009;Geue, et al, 2014;Grant et al, 2011;Kinoshita et al, 2015;Smith et al, 2013;Westby et al, 2016). In the present study, gender as a biological variable was used to measure characteristics of the individual.…”
Section: Conceptual Frameworkmentioning
confidence: 92%